THEMIS measurements of quasi‐static electric fields in the inner magnetosphere. Issue 12 (18th December 2014) - Califf, S.; Li, X.; Blum, L.; Jaynes, A.; Schiller, Q.; Zhao, H.; Malaspina, D.; Hartinger, M.; Wolf, R. A.; Rowland, D. E.; Wygant, J. R.; Bonnell, J. W.
Abstract We use 4 years of Time History of Events and Macroscale Interactions during Substorms (THEMIS) double‐probe measurements to offer, for the first time, a complete picture of the dawn‐dusk electric field covering all local times and radial distances in the inner magnetosphere based on in situ equatorial observations. This study is motivated by the results from the CRRES mission, which revealed a local maximum in the electric field developing near Earth during storm times, rather than the expected enhancement at higher L shells that is shielded near Earth as suggested by the Volland‐Stern model. The CRRES observations were limited to the duskside, while THEMIS provides complete local time coverage. We show strong agreement with the CRRES results on the duskside, with a local maximum near L = 4 for moderate levels of geomagnetic activity and evidence of strong electric fields inside L = 3 during the most active times. The extensive data set from THEMIS also confirms the day/night asymmetry on the duskside, where the enhancement is closest to Earth in the dusk‐midnight sector, and is farther away closer to noon. A similar, but smaller in magnitude, local maximum is observed on the dawnside near L = 4. The noon sector shows the smallest average electric fields, and for more active times, the enhancement develops near L = 7 rather than L = 4. We also investigate the impact of the uncertain boom‐shorting factor on the results and show that while the absolute magnitude of the electric field may be underestimated, the trends with geomagnetic activity remain intact.